Chinese Ice Cream in Indonesia: Analyzing Halal Brand Image, Halal Brand Loyalty, Halal Brand Trust and Purchase Intention - Burhanudin Burhanudin; Reza Nur Saifullah Daldiri (Universitas Pendidikan Indonesia, 2023)
Beverages and ice cream have emerged as a current trend favored by some consumers. However, research on halal drinks and ice cream in Indonesia is still limited. The purpose of this study is to examine the impact of the halal brand image on halal brand loyalty and halal brand trust, and subsequently, on purchase intention. This research employs a consumer survey to explore the relationships between these variables. The study focuses on respondents who are Muslims and have purchased one of Mixue's products, totaling 208 participants. The analysis method employed in this study is PLS-SEM. The results of the analysis reveal a significant influence of halal brand image on both halal brand loyalty and halal brand trust. Furthermore, halal brand loyalty significantly affects purchase intention, whereas halal brand trust does not show a significant impact on purchase intention. Halal brand loyalty, but not halal brand trust, mediates the relationship between halal brand image and purchase intention.